Clostridium difficile multidisciplinary team root cause analysis: impact on clinical care and circumvention of financial penalties posed by clinical commissioning groups, but at what cost?. Issue 2 (March 2018) - Saeed, Kordo; Petridou, Christina; Gray, Hazel; Dryden, Matthew; Davis-Blues, Karen; Lucero, Sheryl; Parker, Natalie; Keyser, Taryn; Matthews, Tanya; Cortes, Nick; Kidd, Stephen; Thomas, Claire; et al.
Background: In Hampshire Hospitals NHS Foundation Trust, in addition to an on-the-spot investigation into hospital-onset Clostridium difficile infection (CDI) by the infection prevention team, a multidisciplinary team root cause analysis (MDT-RCA) forum has been developed. The MDT-RCA aims to deliver a more thorough investigation into individual cases and the recommendation of cases to the clinical commissioning groups (CCG) appeals panel against potential financial penalties (£10, 000 per breached case). We mainly aimed to investigate the financial impact of MDT-RCAs to the Trust. Methodology: Over two years, 84 cases of hospital-onset CDI cases were reviewed by the MDT-RCA forum. Results: Among this cohort, no additional learning outcomes were identified by the MDT-RCAs over those that were found by on-the-spot investigations. In total, 543 staff members attended the MDT-RCAs at a potential cost to the Trust of £23, 795.74–£51, 670.10. The Trust appealed against financial penalties for 27 cases and 14 were successful, i.e. £140, 000 would have been avoided had targets been breached by 14 cases. However, targets were only breached by two cases, meaning only £20, 000 in fines was avoided. Deducting this from the total costs of the MDT-RCA meant the Trust lost £3, 795.74–£31, 670.10. Conclusion: Over the two years reviewed, the MDT-RCA proved to be costly to the Trust, with no additional learning or quality improvement measures identified.